Ancestral technological solutions and their application in current times - Barbachán Ruales, Enrique Alejandro (2022)
The present work aims to recognize and revalue the technological solutions that our ancestors applied in accordance with the environment in order to be applied in current times. Quantitative research, of a descriptive type with an ethnographic, technological method, applied to students, teachers and university graduates in the technological and engineering area. The sample is non-probabilistic through convenience sampling. Concluding that, effectively, our ancestors applied various technological solutions in accordance with their environment, among which we find, for the metallurgical mining aspect, the Huayras; in the treatment and planting of water las Amunas; in infrastructure, earthquake-resistant technologies using mesh bags or Shicras; in soil and water management, the waru warus, production in floodplain or riverside areas, agriculture in Amazonian Várzea soils, these technologies have application in current times, which would be profitable and convenient in an eco system. sustainable, only 22% of those surveyed have knowledge of these technologies, so it is necessary to teach them from basic education.